Ethics and entrepreneurship - Harris, Jared D.; Sapienza, Harry J.; Bowie, Norman E. (Journal of Business Venturing, 2009)
As the study of entrepreneurship and the study of business ethics become increasingly established, the intersection of entrepreneurship and ethics is receiving increasing scholarly attention. In this paper, we review the research connecting ethics and entrepreneurship, classifying the literature into three broad themes; we also identify and integrate the key themes that emerge, and we offer suggestions for future research. We conclude by introducing the articles in this special issue.